The Dutch Navy of the Seventeenth and Eighteenth Centuries. - Bruijn, Jaap R. (Research in Maritime History LUP., 2017)
This book is a reprint of Jaap R. Bruijn's 1993 book, The Dutch Navy, which offers an English-language overview of the history of the Dutch Navy in the seventeenth and eighteenth centuries.